Rancang Bangun Aplikasi Presensi Karyawan Berbasis Mobile Menggunakan Flutter, Swafoto, dan Dengan Backend XAMPP - Reyhan Mahendra; Jibran Dwi Andara; Muhammad Rafli (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
Manual employee attendance management remains widely used, despite its vulnerability to data manipulation, delayed recaps, and limited location flexibility. This study aims to design and develop a cross platform mobile attendance application using the Flutter framework, equipped with a selfie photo feature as visual proof of attendance and the Global Positioning System (GPS) for real-time location validation through a geofencing mechanism. Data management is handled using a XAMPP backend consisting of the Apache web server, PHP programming language, and MySQL database management system. Communication between the Flutter application and the server uses an HTTP-based RESTful API with JSON as the data exchange format. The software development method employed is the Waterfall model. Testing was conducted through Black-Box Testing covering 35 test scenarios and User Acceptance Testing (UAT) involving 40 respondents. Black-Box Testing results showed all scenarios passing with a 100% pass rate. The UAT yielded an average score of 86.8 out of 100, categorized as Very Good. GPS validation accuracy averaged 95.5%, while the attendance processing time efficiency improved by 68.4% compared to the manual system.